Effects of garlic (Allium sativum) and ginger (Zingiber officinale) powder and their combination on antioxidant and hematological response in sheep - Allu, R. P. (2022)
Garlic and ginger as herbs exhibit strong antioxidant and immunological properties, but their combination may have a complementary role on each other. This study was done to assess the complementary effect of supplementing garlic and ginger powder on the antioxidant status and physiological response of sheep. Sixteen (16) mixed breed rams were maintained on four experimental diets in a completely randomized design for 84 days. The four diets were Control (no garlic or ginger powder), GaP (garlic powder 2.5 g/kg diet), GiP (ginger powder 2.5 g/kg diet) GGP (garlic powder 1.25 g/kg diet + ginger powder 1.25 g/kg diet). A one-way analysis of variance as contained in the GLM of SPSS (version 23) was used to analyze data on hematological parameters, serum indices, serum mineral concentration, and oxidative stress biomarkers of the sheep. Findings from the results revealed a reduction (p<0.05) in red blood cell total protein and serum concentrations of sodium and calcium in the herbal groups. The reduction (p<0.05) in the concentration of manganese, iron, and zinc in the ginger powder group was enhanced (p<0.05) by its combination with garlic powder. Albumin, superoxide dismutase and malondialdehyde concentrations as markers of oxidative stress were enhanced (p<0.05) in the herbal combination group compared to only the garlic group. Nitric oxide concentration further reduced in the herb combination group compared to feeding garlic or ginger alone. The combination of garlic and ginger powder gave optimum immunological and anti-oxidant responses than feeding only garlic or ginger. The combination of 1.25 g/kg diet of garlic and ginger each would achieve an overall better anti-oxidant and immunological performance in sheep than feeding 2.5 g/kg diet of garlic or ginger singly.